Adaptability of Teacher’s Quarters Using IBS in Malaysia - Zulkefle Ismail (Journal of Architecture, Planning and Construction Management, 2020)
The objective of this paper is to identify the Performance Index of Satisfaction (PIS) on adaptability of housing using Industrialized Building System (IBS) in Malaysia. Preliminary research identified that the attitude of the individual towards design standard and userâ€™s need depends on many varying factors such as physical area and psychological feeling of the internal spaces. The study focuses on the housing using IBS by identifying level of userâ€™s satisfaction and the conditions for adaptability to be applied into the house. Adaptability in architecture is defined as providing occupants with forms and means that facilitate a fit between their space needs and the constraints of their homes either before or after occupancy. The ability of modifications to suit new conditions or the design will allow for any additions to make building more flexible. This will ease for renovation and extension thats currently limited in housing using IBS. A case study was carried out at eleven Teacherâ€™s Quarters using IBS in Malaysia. The Performance Index of Satisfaction (PIS) is utilized in the analysis as a systematic manipulation of the factors and the variables of design. The findings confirmed the requirements and potential for physical adaptabilities in Teacherâ€™s Quarters. The conceptual model was revised based on userâ€™s satisfaction of internal spaces in the house. Transforming the architectural dictums from â€œform follows functionâ€ to â€œform accommodates changeâ€ by estimating the sociological impact of professional and practice attitudes and mindsets should be encouraged towards successful implementation of adaptable housing using IBS in Malaysia.